Areca Seed Germination Response Due to Seed Storage and Moisturizing - Muh Duwi Lesmana; Tantri Palupi; Elly Mustamir (Fakultas Pertanian Universitas Tanjungpura, 2020)
ABSTRACT This study aims to determine the response of areca seed germination to the storage and moisturizing time of seeds and to determine the best storage and moisturizing time of areca seed in accelerating the time of germination. This research was conducted in a private land located at Jalan Tanjung Raya 2 East Pontianak, Banjar Serasan Village. This research was conducted from December 9, 2018, until March 20, 2019, starting from seed collection until the end of the study. This study uses a field experiment method with a Completely Randomized Design (CRD) consisting of one factor, namely: P1 = stored for 7 days + moisturized for 4 days, P2 = kept for 7 days + humidified for 6 days, P3 = stored for 14 day + moisturized for 4 days, P4 = stored for 14 days + moisturized for 6 days, P5 = stored for 21 days + moisturized for 4 days, P6 = stored for 21 days + moisturized for 6 days, P7 = stored for 28 days + moisturized for 4 days, P8 = stored for 28 days + moisturized for 6 days, P9 = stored for 35 days + moisturized for 4 days, P10 = stored for 35 days + moisturized for 6 days, P0 = not stored + not moisturized (control), Of the 11 treatments repeated 3 times so that there were 33 experimental units, and each unit used 10 seeds then there were 330 seeds. All seeds will be germinated in a dark condition, except treatment P0. The variables observed were water content (%), vigor index (%), germination (%), growth speed (% / etmal), growth simplicity (%), shoot length (cm), root length (cm). The results of this study showed the response of areca seed germination due to seed storage and moisturizing significantly affected all observed variables, P1 treatment (7 days storage and 4 days moisturized) had the best average treatment results and was more efficient on all observational variables namely vigor index 100%, simultaneity grew 100%, germination capacity of 100%, speed of growing 8.21% / etmal, shoot length 26.00 cm, and root length 22.18 cm. Keywords: Germination, Storage of Seed, Moisturizing of Seed, Areca, Seed.